The Effects of Grain Size, Oxidizers and Catalysts on Band Gap Energy of Gelam-Wood Carbon - Syarif, Nirwan; Rohendi, Dedi; Haryati, Sri; Dewi, Claudia (http://dx.doi.org/10.31427/IJSTT.2019.2.2.5, 2019)
The research of the effects of grain size, oxidizers, and catalysts on band gap energy of gelam-wood carbon has been conducted in which the carbons were produced from gelam-wood pyrolysis in high temperatures. The instrumentations used in this study were UV-Vis, FTIR spectrophotometer, and SEM. SEM and FTIR were used to characterize the morphology and the functionality of the carbon surface. UV-Vis spectrograms showed that the electronic property of carbon such as band gap was affected when grain size and surface area were changed. The increase of the functional groups in carbon occurred as the surface area of the carbon was increased. Band gap energy of crystalline carbon became much lower along with the increase in grain size due to the effects of bands-broadening. FTIR spectrograms showed that the carbon contained of hydroxyl and carboxylic groups. The hydroxyls were derived from steam-oxidized carbon that was provided narrower in the interlayer distance and lower-set band gap energy. Carboxylic groups were derived from acid nitric oxidation causing flat layer to become curved. The layers were wider and the band energy was higher. The main factor that affects the electronic structure of metal oxide in carbon/metal oxide composites was atomic alignments. The band gap energy increased along with the increase of the asymmetry alignments in metal oxide.